2022
DOI: 10.4111/icu.20210472
|View full text |Cite|
|
Sign up to set email alerts
|

Focal therapy for prostate cancer with irreversible electroporation: Oncological and functional results of a single institution study

Abstract: Purpose Focal irreversible electroporation (IRE) for prostate cancer aims to reduce quality of life complications, however outcomes data remains limited. We aimed to evaluate histological in-field clearance of prostate cancer at ≥12 months post-IRE. Materials and Methods Retrospective review of prospectively acquired data of consecutive patients treated between August 2018 and August 2021. Significant recurrence was defined as a ≥6 mm core Gleason 3+3, or ≥Gleason 3+4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
3
12
0
2
Order By: Relevance
“…However, the slightly higher progression rate in our present study might be explained by the higher standardised biopsy rate (83% vs 36%), lower threshold for progression to salvage treatment and consequently lower metastatic disease burden (0.4% vs 1.6%). Recently, Yaxley et al [12] published their initial experience on 64 IRE patients, externally validating the results of our series by obtaining comparable results. Table 2 Multivariable Cox proportional hazard analysis on the risk to develop a failure during follow-up (progression to radical treatment and/or systemic disease).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, the slightly higher progression rate in our present study might be explained by the higher standardised biopsy rate (83% vs 36%), lower threshold for progression to salvage treatment and consequently lower metastatic disease burden (0.4% vs 1.6%). Recently, Yaxley et al [12] published their initial experience on 64 IRE patients, externally validating the results of our series by obtaining comparable results. Table 2 Multivariable Cox proportional hazard analysis on the risk to develop a failure during follow-up (progression to radical treatment and/or systemic disease).…”
Section: Discussionsupporting
confidence: 76%
“…Recently, Yaxley et al. [12] published their initial experience on 64 IRE patients, externally validating the results of our series by obtaining comparable results.…”
Section: Discussionsupporting
confidence: 76%
“…Of these patients one had a salvage robot-assisted radical prostatectomy, two commenced androgen deprivation therapy (ADT) and one remained on surveillance. The median (IQR) time to salvage therapy was 15 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) months). The remaining six patients (16%) developed metastatic disease, of which four had residual local disease while two did not.…”
Section: Oncological Outcomesmentioning
confidence: 99%
“…Conversely, results from a smaller series reported by Yaxley et al. [ 25 ] found that risk of in‐field recurrence on biopsy for men with high‐grade PCa after focal IRE was low (none of seven patients).…”
Section: Discussionmentioning
confidence: 85%
“…A high-risk cohort from a focal HIFU series by Reddy et al [24] found that of 386 patients, 65% had failure-free survival at 7 years and 73% had no salvage (local or systemic) treatment at 7 years. Conversely, results from a smaller series reported by Yaxley et al [25] found that risk of in-field recurrence on biopsy for men with high-grade PCa after focal IRE was low (none of seven patients).…”
Section: Patient Selectionmentioning
confidence: 75%